Human-macaque conflicts at a human settlement in Riau Province, Indonesia - ARYA ARISMAYA METANANDA; SUTOPO SUTOPO; GUNAWAN GUNAWAN; NURJAMAN NURJAMAN; RAHMAD DANI; YAHYA RUHYAT; SUTOPO SUTOPO; AHMAD AHMAD; ANDI APRIANTO; JHONSON NAIBAHO; WHISNU FEBRY AFRIANTO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Metananda AA, Sutopo, Gunawan, Nurjaman, Dani R, Ruhyat Y, Sutopo, Ahmad, Aprianto A, Naibaho J, Afrianto WF. 2024. Human-macaque conflicts at a human settlement in Riau Province, Indonesia. Biodiversitas 25: 2950-2958. Various human activities have caused the loss and degradation of the natural habitat of macaques, resulting in their share habitat with high levels of human activities. The proximity of macaque habitats to human activities may increase potential human-macaque conflicts. This research aims to observe the conflict between humans and macaques, especially Macaca fascicularis (Raffles 1821), by identifying macaque population parameters, including the number of groups, group distribution, home range, sex ratios, and age structure in the Pertamina Official Housing (POH) complex, Dumai District, Riau Province, Indonesia. Population data were acquired through a census inventory using concentration count and exploration methods. The results showed the population of 461 macaque individuals belonging to 19 groups which were spread over 17 points in the study area. Based on the sex ratio, juveniles were the most predominant group with 104 individuals. The distribution of individuals indicated that there were several groups with varying numbers and structures at one observation point. Factors that caused macaque disturbance include food availability, habitat space availability, community habits and behavior, and safety. Macaque disturbance included attacks on children, damage to lighting, roofs, fruit trees, vegetable plants, and the presence of M. fascicularis groups in large numbers in the area traversed by residents. We recommend improving the management of M. fascicularis habitat, conducting population control, and educating the community about behaviors that can trigger disturbances. In addition, mitigation measures and regular monitoring must be carried out to find effective long-term solutions.